2017
DOI: 10.1007/s10661-017-6234-6
|View full text |Cite
|
Sign up to set email alerts
|

Applying the change vector analysis technique to assess the desertification risk in the south-west of Romania in the period 1984–2011

Abstract: The desertification risk affects around 40% of the agricultural land in various regions of Romania. The purpose of this study is to analyse the risk of desertification in the south-west of Romania in the period 1984-2011 using the change vector analysis (CVA) technique and Landsat thematic mapper (TM) satellite images. CVA was applied to combinations of normalised difference vegetation index (NDVI)-albedo, NDVI-bare soil index (BI) and tasselled cap greenness (TCG)-tasselled cap brightness (TCB). The combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Thus, NDVI-albedo can be characterized as the most appropriate index combination for detecting the land cover changes in the study area. This finding is in agreement with the results from the research work of Vorovencii [33]. Specifically, by applying CVA for three different index combinations (NDVI-albedo, NDVI-brightness index and TCG-TCB), it was concluded that the most accurate outputs were obtained from the combination of NDVI-albedo.…”
Section: Discussion and Interpretationsupporting
confidence: 90%
See 1 more Smart Citation
“…Thus, NDVI-albedo can be characterized as the most appropriate index combination for detecting the land cover changes in the study area. This finding is in agreement with the results from the research work of Vorovencii [33]. Specifically, by applying CVA for three different index combinations (NDVI-albedo, NDVI-brightness index and TCG-TCB), it was concluded that the most accurate outputs were obtained from the combination of NDVI-albedo.…”
Section: Discussion and Interpretationsupporting
confidence: 90%
“…The outputs of CVA were evaluated by confusion matrices in terms of accuracy [33,34]. A confusion matrix provides accuracy statistics such as kappa index (with a range from 0 to 1 indicating from very low to excellent accuracy) and overall accuracy, according to the proportion of an area that is correctly matched with reference data [35].…”
Section: Accuracy Assessmentmentioning
confidence: 99%
“…Desertification is the focus of environmental issues of concern to the world today, and its hazard ranks first among the top ten disasters in the world (Vorovencii, 2017). The expansion of deserts engulfs productive arable land, resulting in harsh sand and dust climates, leading to poverty and ecological migration (Xue et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Using UASs equipped with small thermal, laser, or optical sensors has emerged as a promising alternative to obtaining 3D models, and is more frequently being used in forestry applications [5]. Data processing techniques makes it possible to use high-resolution images and 3D data in forest monitoring activities [6][7][8][9][10][11], as well as in taking forest inventory and remotely measuring tree variables [1,[12][13][14]. Several studies have focused on estimating the biometric characteristics of either forest stands [15] or individual trees by means of the segmentation of digital models [11,16].…”
Section: Introductionmentioning
confidence: 99%